(untitled) (Global Journal of Medical Research, 2014)
Draining cutaneous sinus tracts in the area of face may be caused by chronic dental infections. Misdiagnosis of these cutaneous sinus tracts usually leads to destructive invasive treatment of the skin lesions that is not curative. Diagnosis of the cause may be challenging but is the key to successful therapy. Successful repair depends primarily on removal of etiological factors. This scientific paper aims to present a case, treated successfully & closure of the tract achieved by conventional root canal therapy.